Estratégias de reprodução social dos agricultores familiares assentados em Santana do Livramento/RS - (:unkn) unknown (Universidade Federal do Pampa, 2019)
The Family agriculture has been changing over the past few years. In Brazil, this social category stands out in the 1990s, when several studies clarify the “backward” character of the segment and demonstrate the need for public policies focused on family agriculture. Thus, this study aimed to analyze the strategies of social reproduction of family farmers settled in Santana do Livramento/RS. The methodology is based on qualitative research focusing on exploratory character which the case study method was used. It was accomplished eleven interviews with farmers settled in three counties. Likewise, bibliographical and documental research,and non-participant observation were accomplished. In order to analyse the data it was used an approximation of the technique of content analysis. The data revealed that the Family agriculture settled in Santana do Livramento/RS started in the beginning of 1922 with farmers from the north of the State, the area where started the process of agricultural modernization. Furthermore, the farmers settled in the county embrace consciously and rationally many strategies concerning social reproduction, whether agricultural or not, such as diversification, auto consumption production, pluriactivity, among others. It is also observed that the social reproduction strategies adopted by the farmers interviewed, besides being diversified, hardly change from one settlement to another. For the use of the strategies, the farmers interviewed take into consideration the needs of the family, the land productivity, location, personal knowledge, access to public policies, life experience, among other issues. Despite the introduction of several settlements in the county, the settled family farmers still face many difficulties to remain in rural area, therefore, it is necessary the Government takes on the responsability as the main supporter of rural development.
Keywords: Administração; Agricultura familiar; Reprodução social; Assentamento rural; Administration; Rural settlements; Family agriculture; CNPQ::CIENCIAS SOCIAIS APLICADAS